Reconceptualizing Latin American authoritarianism in the 1970 : from bureaucratic-authoritarianism to neoconservatism - Schamis, Hector E. (1991)
Los golpes de Estado y dictaduras militares en : Argentina, Brasil, Chile y Uruguay
Keywords: Autoritarismo; Conservadurismo; América Latina